Clinical features and prevalence of hiv, hepatitis b and hepatitis c infections in patients with opioid use disorder - Keskin, Necla; Güzel, Yağmur (Journal of Dependence, 2025)
Objective: The aim of this study was to determine the prevalence rate of HBV, HCV, and HIV, along with sociodemographic and clinical characteristics in patients with opioid use disorder. Method: The study sample consisted of 244 inpatients diagnosed with opioid use disorder. A data form documenting the socio-demographic features and clinical characteristics of opioid use disorder was completed. Routine blood and urine drug test results were retrieved from the hospital information system. The sample group was divided into two categories based on anti-HCV seropositivity, and the groups were compared according to socio-demographic features, clinical characteristics, and laboratory findings. Results: 9% of the sample group was anti-HCV positive, and the rate of HBsAg positivity was 0.8%. All patients tested negative for anti-HIV. Patients infected with HCV were male, older (36.4±10.2 vs. 30.8±10.5), and had more comorbid physical disorders (68.2%). Use of injectable drugs over a lifetime (77.3%), in the last year (36.4%), and/or in the last month (27.3%) was related to an increased risk of HCV infection. Conclusion: Female patients with opioid use disorder are estimated to be underrepresented and undertreated. As older age and intravenous drug use increase the risk of hepatitis C infection, and comorbid physical disorders are more prevalent in patients with HCV, screening programs and preventive approaches are crucial for this patient group.